Effect of surface treatment and stacking sequence on mechanical properties of basalt/glass epoxy composites. Issue 4 (May 2019) - Raajeshkrishna, CR; Chandramohan, P; Saravanan, D
In the present work, sandwich hybrid composites have been fabricated using hand layup technique followed by compression molding process. Glass and basalt fabrics were used with epoxy resin to fabricate the sandwich composites. The fabrics were used in both untreated and treated conditions using hydrochloric acid and sodium hydroxide solutions. The Fourier transform infrared study conducted on the fabrics before and after the surface treatment shows the effectual impregnation of acid and base on the fabric by the formation of ions on the surfaces. The tensile and hardness tests were conducted as per the ASTM D638-10 and ASTM D2240 standards. The results show that hybridization and surface treatment improve tensile strength and hardness in all the composites. In particular, the hydrochloric acid–treated sandwich composites with basalt fabric as core and glass fabric as skin have recorded the highest tensile strength of 356.39 MPa. The experimental values have been validated using the simulation results of finite element analysis in ANSYS 15.0 with a minimum deviation of 0.47%.